2023
DOI: 10.1186/s13047-023-00631-1
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of randomised controlled trials on surgical treatments for ingrown toenails part I: recurrence and relief of symptoms

Victoria Exley,
Katherine Jones,
Grace O'Carroll
et al.

Abstract: Background Ingrown toenails are a common nail pathology. When conservative treatments are ineffective, a surgical approach is often utilised. Despite recent narrative reviews, there is a need for an up-to-date and rigorous systematic review of surgical methods for treating ingrown toenails. Methods Five databases (MEDLINE, Embase, CINAHL, Web of Science and CENTRAL) and two registers (Clinicaltrials.gov and ISRCTN) were searched to January 2022 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…Findings from this paper should be interpreted in line with the assessments of risk of bias and certainty of evidence reported in the first paper [15]. All studies included in the review were assessed as having either high risk or having some concerns about bias when assessed with the Cochrane ROB 2.0 tool.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Findings from this paper should be interpreted in line with the assessments of risk of bias and certainty of evidence reported in the first paper [15]. All studies included in the review were assessed as having either high risk or having some concerns about bias when assessed with the Cochrane ROB 2.0 tool.…”
Section: Discussionmentioning
confidence: 86%
“…Studies were restricted to English, pertaining to human participants, and must have reported one of the pre‐defined outcomes for inclusion. Our co‐primary outcomes were relief of symptoms, and symptomatic regrowth (nail spicules/nail spikes), which are reported elsewhere [15]. Secondary outcomes: healing time, post‐operative complications (e.g., infection and haemorrhage), pain of operation, post‐operative pain (duration and intensity) and participant satisfaction are reported herein.…”
Section: Methodsmentioning
confidence: 83%
See 3 more Smart Citations